A bone hairpin with the head carved in the shape of a female bust now housed in the Archaeological Museum in Milan (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2022)
The Civic Archaeological Museum of Milan holds a bone hairpin with the head carved in the shape of a female bust that can be inserted into a series of examples which, chronologically, can be placed in 4th century A.D. The hairstyle portrayed is a simplified variation of the style known as “Scheitelzopffrisur” in which the hair was gathered into braids and placed in more or less wide bands, positioned upwards from the neck at the rear of the head to the top where they were held firm in a final fold. This hairstyle, in all its various evolutions, has been amply documented on statues and coins with female portraits. It was already evident in the first half of the 3rd century A.D. and became widespread in alternating phases, in the second half of the century and throughout the 4th century A.D. There are numerous bone hairpins portraying this hairstyle and the article examines in detail the comparisons and different variations documented.
Keywords: hairpin; bone; female bust; hairstyle